Omega-3 Polyunsaturated Fatty Acids as Adjunctive Therapy to Antipsychotic Treatment in Adults with Schizophrenia: A Systematic Review and Meta-Analysis - Aura Patricia Yepes Yepes Sarmiento; Thayra Gomez; Kimberly Barrios; Hernan F. Guillen-Burgos (Brain Sciences, 2026)
Background/Objectives: Schizophrenia causes substantial disability and reduced life expectancy, while symptoms frequently persist despite antipsychotic treatment. Long-chain n-3 polyunsaturated fatty acids (n-3 PUFAs) have been proposed as adjunctive therapy because of their anti-inflammatory and neurobiological properties. This systematic review and exploratory meta-analysis evaluated the efficacy and safety of adjunctive n-3 PUFAs in adults with schizophrenia. Methods: The review followed PRISMA 2020 and was prospectively registered in PROSPERO (CRD420251178174). PubMed, Web of Science, Scopus, Ovid, CENTRAL, ClinicalTrials.gov, and ICTRP were searched without language or date restrictions. Randomized controlled trials of n-3 PUFAs added to antipsychotic therapy were included. Risk of bias was assessed using RoB 2. PANSS scores were pooled as mean differences (MDs) using an inverse-variance random-effects model with REML estimation; dichotomous outcomes were pooled as risk ratios (RRs) using an inverse-variance random-effects model with the DerSimonian–Laird estimator or a fixed-effect model with the Mantel–Haenszel method, with a 0.5 continuity correction for zero cells. Results: Of 301 records, 10 randomized controlled trials met the eligibility criteria. Where sufficient comparable data were available, exploratory meta-analyses were conducted. Only one trial provided strict intention-to-treat final PANSS total data. A two-trial sensitivity meta-analysis (116 participants) showed no significant reduction in final PANSS total scores (MD −5.04, 95% CI −14.16 to 4.08; I2 = 55.8%). Results were also nonsignificant for clinical response (RR 1.62, 95% CI 0.27–9.78), all-cause discontinuation (RR 1.32, 95% CI 0.31–5.65), and discontinuation due to adverse events (RR 1.35, 95% CI 0.38–4.81). Extreme sensitivity analyses remained nonsignificant. Subgroup signals involving clozapine or baseline fatty-acid status were not consistently replicated. Evidence was limited by few studies, attrition, and substantial heterogeneity in n-3 PUFA formulation, dose, duration, population, and concomitant antipsychotic therapy. Conclusions: Current evidence does not support routine adjunctive n-3 PUFAs for symptom reduction in adults with schizophrenia. The available data cannot identify an optimal EPA/DHA formulation, dose, or responsive clinical subgroup; larger biomarker-informed trials are needed.